Modern development on the features of magnetic field and heat sink/source in Maxwell nanofluid subject to convective heat transport - Irfan, M.; Khan, M.; Khan, W.A.; Ayaz, M. (Physics letters. A, 2018)
•Stretching cylinder.•Steady 2D flow of Maxwell nanofluid is modeled.•The effects of magnetic field and heat sink/source are considered.•Convective boundary conditions is considered here.•Analytical solutions are established through HAM technique. Nanofluids are forthcoming new generation heat transfer fluids, which have been scrutinized precisely, in current years. Thermophysical assets of these fluids have noteworthy impact on their heat transfer features. In this current investigation a mathematical relation for two dimensional (2D) flow of magnetite Maxwell nanofluid influenced by a stretched cylinder is established. To visualize the stimulus of Brownian moment and thermophoresis phenomena on Maxwell fluid Buongiorno's relation has been considered. Moreover, heat sink/source and convective condition are also presented for heat transport mechanism. The homotopic scheme has been developed for the solutions of nonlinear ordinary differential equations (ODEs). The achieved outcomes are planned and consulted in aspects for somatic parameters. It is noteworthy that the velocity of Maxwell fluid display conflicting performance for curvature parameter and Deborah number. It is also reported that the liquid velocity decays for magnetic parameter, whereas the nanoliquid temperature and concentration field enhance for magnetic parameter. Furthermore, the liquid temperature intensifies for the progressive values of thermophoresis parameter and Brownian motion. Additionally, endorsement of current significances is organized via benchmarking with earlier famous limiting situations and we pledge a marvelous communication with these outcomes.